2017
DOI: 10.3371/csrp.cbmf.071317
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stigma on subjective well-being in people with mental disorders

Abstract: Positive self-concept protects the person from the harm that stigma may cause on his well-being. It especially protects positive affect, which we propose is an important resource in the recovery process. These findings have clinical and research implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Further reflecting on our theme, Effects of Stigma on the Self and Wellbeing , it is worth noting that stigma had an important influence on self-esteem and self-worth in our sample, an observation that echoes studies in young people [ 7 , 73 , 76 , 82 , 99 ]. Past research has also found links between experiences of mental health stigma and reduced wellbeing [ 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…Further reflecting on our theme, Effects of Stigma on the Self and Wellbeing , it is worth noting that stigma had an important influence on self-esteem and self-worth in our sample, an observation that echoes studies in young people [ 7 , 73 , 76 , 82 , 99 ]. Past research has also found links between experiences of mental health stigma and reduced wellbeing [ 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…Second, our research shows that internalized stigma fully mediates the relationship between perceived individual discrimination and self‐esteem. This result replicates those showing evidence of a negative association between internalized stigma and self‐esteem in people with mental illness (Corrigan et al, 2006; Morgades‐Bamba, Fuster‐RuizdeApodaca, & Molero, 2017) and shows that stigma awareness is not directly associated with well‐being; rather, it is the internalization of stigma that is associated with self‐esteem and self‐efficacy (Corrigan & Rao, 2012; Muñoz et al, 2011; Watson et al, 2007). Despite the expected negative consequences of concealment, no direct or mediating effects on self‐esteem were found.…”
Section: Discussionsupporting
confidence: 87%
“…The negative association between perceived personal discrimination and self-esteem has be found in other devalued groups such as women (Bourguignon et al, 2006; Kobrynowicz & Branscombe, 1997), African Americans (Postmes & Branscombe, 2002), and African immigrants in Belgium (Bourguignon et al, 2006). There is also evidence of a negative association between internalized stigma and self-esteem in people with mental illness (Corrigan et al, 2006 or Morgades-Bamba, Fuster-Ruizdeapodaca, & Molero, 2017) and people with HIV (Lee et al, 2002). Our results are consistent with the proposition that internalized stigma fully mediates the relationship between personal discrimination and self-esteem that, as far as we know, is new to the literature.…”
Section: Discussionmentioning
confidence: 99%